Development of Flight Multifunctional Indicator Based on A320 and B737 NG Flight Indicator - A R Pandie; A V Kirillov (Institut Teknologi Bandung, 2021)
The objectives of this research are: to know the concept of modeling and simulation the cockpit display based on disadvantages and differences between A320 and B737NG; to offer the development and new technology to design the development (new) flight instruments of the display based on Airbus A320 and Boeing B737 NG flight instrument technology. Methodologies that have been used in this research are literature review, interview/discussion/questionnaire, and descriptive analysis. Questionnaire towards the users/pilots who flies airplane A320 or B737 NG. For the questionnaire, the Likert-scale method is utilized to collect data and information. This research result’s in finding that: 1. the technology of flight instrument system between A320 and B737 NG visually displays similarity with several differences such as ergonomic side, ECAM technology, and VSD technology. 2. Based on works of literature review and response from the users/pilots, the author finds and proposes several technologies or requirements to apply in the new type model of PFD and Multi-function Display, they are including: PFD and MFD merged into one display only with some additional menu buttons; ECAM + engine warning display, ECAM + systems display, and digital instruction to solve the problem merged into one display only with some additional buttons; display design is using the fully digital display, computerized system, LCD technology, VSD, and EHSI technology, and layout display is using configuration “basic T”; standby flight instrument merged into one display only with some additional menu buttons